2023
DOI: 10.1155/2023/5686929
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Rare Ginsenosides and Antioxidant Activity Quality of Ginseng Jiaosu Based on Probiotic Strains and Fermentation Technology

Abstract: The primary active components of plant ginseng are saponins, and rare saponins play a specific antitumor action. In this study, Lactobacillus that can efficiently transform rare saponins were screened as fermentation strains of ginseng enzymes. The fermentation process was optimized to investigate the changes in various biochemical indicators and antioxidant activities of the enzymes before and after fermentation. The results showed that Lactiplantibacillus plantarum had the highest conversion efficiency for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…This enzyme may have catalyzed the conversion of bound flavonoids in the fermentation liquid into free-form flavonoids [39], which would have resulted in a relatively constant level of flavonoids in the fermentation liquid. This result is similar to that of Xu et al [29].…”
Section: Correlation Analysis Of the Active Ingredients And Antioxida...supporting
confidence: 93%
See 1 more Smart Citation
“…This enzyme may have catalyzed the conversion of bound flavonoids in the fermentation liquid into free-form flavonoids [39], which would have resulted in a relatively constant level of flavonoids in the fermentation liquid. This result is similar to that of Xu et al [29].…”
Section: Correlation Analysis Of the Active Ingredients And Antioxida...supporting
confidence: 93%
“…Lee et al [ 28 ] found that fermentation can improve the antioxidant activity of ginseng when studying the antioxidant effect of fermentation on ginseng, which is consistent with the results of this experiment. Xu et al [ 29 ] found that LAB can produce certain active substances during metabolism, which efficiently scavenge free radicals extracellularly. This may explain the increase in antioxidant activity observed as a result of ginseng fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…Research by Xu et al demonstrated that fermentation by L. plantarum enhances the conversion efficiency of diol saponins and increases the content of rare ginseng saponin-CK by 256%. This further confirms the ability of lactobacilli fermentation to enhance anti-tumor functionality through the bio-transformation of active substances [127].…”
Section: Anti-tumor Functionsupporting
confidence: 71%